The Effect of Enterprise Risk Management and Corporate Social Responsibility on Firm Value - Salsabila, Jihan; Septiyanti, Ratna (International Journal of Economics, Business and Innovation Research, 2024)
This study examines the effects of Enterprise Risk Management (ERM) and Corporate Social Responsibility (CSR) on firm value in Indonesia's mining sector, specifically analyzing publicly listed companies from 2018 to 2022. Utilizing Tobin's Q ratio to measure firm value, the research employs multiple linear regression to explore the interactions among ERM, CSR, and Return on Equity (ROE) as a control variable. Results indicate a significant negative relationship between ERM disclosure and firm value, implying that poor communication of risk management may erode investor confidence. In contrast, CSR reveals a significant positive impact on firm value, reinforcing stakeholder theory's emphasis on addressing economic, social, and environmental issues. The study concludes that while effective CSR strategies can enhance corporate value, current ERM practices may detract from it. Additionally, ROE does not significantly effect firm value, highlighting the need for mining companies to strengthen risk communication and CSR efforts to enhance investor confidence and overall corporate value.